PEMBERIAN BLOTONG PADA MEDIA SERBUK GERGAJI UNTUK BUDIDAYA JAMUR TIRAM (Pleurotus ostreatus) - Donny Christal Ginting Suka; Idwar '; Armaini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Research giving of filter cake on sawdust medium for the cultivation of oyster mushroom (Pleurotus ostreatus) aims to increase the production of oyster mushroom to the best, and determine the best dose will increase the production. This research has been conducted in the village of Kubang raya of Siak Hulu Kampar district in Riau Province in July through September of 2013 this research was carried out experimentally using a complete randomized design (CRD) comprising administering a dose of 5 treatments in the filter cake: Without giving a dry filter cake (control), giving 20 g / baglog, 40 g / baglog, 60 g / baglog, 80 g / baglog. The data obtained were further tested by Duncan's New Multiple Range Test (DNMRT) at the level of 5%. Results of analysis of variance showed that administration can affect the filter cake and enhance the enjoyment of the production. The use of a dose of 60 g of filter cake on sawdust medium gave the highest production of oyster mushrooms is 149.33 g / baglog. Keywords: oyster mushrooms, filter cakeABSTRACT Research giving of filter cake on sawdust medium for the cultivation of oyster mushroom (Pleurotus ostreatus) aims to increase the production of oyster mushroom to the best, and determine the best dose will increase the production. This research has been conducted in the village of Kubang raya of Siak Hulu Kampar district in Riau Province in July through September of 2013 this research was carried out experimentally using a complete randomized design (CRD) comprising administering a dose of 5 treatments in the filter cake: Without giving a dry filter cake (control), giving 20 g / baglog, 40 g / baglog, 60 g / baglog, 80 g / baglog. The data obtained were further tested by Duncan's New Multiple Range Test (DNMRT) at the level of 5%. Results of analysis of variance showed that administration can affect the filter cake and enhance the enjoyment of the production. The use of a dose of 60 g of filter cake on sawdust medium gave the highest production of oyster mushrooms is 149.33 g / baglog. Keywords: oyster mushrooms, filter cake